Vozes por trás de corpos : as representações do corpo feminino em contos de Marcelino Freire - Costa, Karine Conte de Mattos da (2021)
This dissertation brings a research of Marcelino Freire's work, covering titles such as Contos Negreiros (2005), Amar é Crime (2011), Angu de Sangue (2005), BaléRalé (2003) and Bagageiro (2018) in search of subaltern women characters who have their stories directly affected by violence and inequality. The focus of the literary analysis is on the representation of the female body and social stereotypes, as well as on power relations and on the discourse expressed through Marcelino's way of narrating. It also focuses on how his writing deviates from conventional patterns through a breakdown of the readers’ expectations and common sense. The changes in the structures of contemporary narratives and the importance of Peripheral Marginal Literature for the representation of subordinate characters within the current literary panorama are also discussed. Studies of concepts relevant to the theme and that go through the use of "a new realism" and its relationship with urban violence are considered as well as the discussions around the place of speech within literature and an authorial function (FOUCALT, 1969) attributed to the writer and the characteristics of the women created in the selected tales that dialogue with the theme of the body and violence. In addition, Marcelino’s literary style, full of orality and performance, is read not only within the written support of the text, but also from the point of view of the repercussion of his personal and media involvement with the values defended in his work. In this way, we try to discuss the importance of the writer for the academic studies of contemporary and peripheral Literature, since his production and performance are of great literary, political and social relevance. In addition, the aim is to discuss problems in the representation of subaltern characters and the creation of spaces, legitimization and sharing of the foci of studies so that there are more and more voices that are in fact heard behind the narrated bodies.